MicroRNA Regulation of Embryonic Stem Cell Pluripotency and Differentiation - Zhou, Xin; Zhou, Xuedong; Zheng, Liwei (Current Stem Cell Research & Therapy, 2015)
Embryonic stem cells (ES cells) hold great potential for regenerative medicine. Grasp of the underlying elaborate machinery is required for clinical application. MicroRNAs serve as important post-transcriptional regulators of various normal and pathological processes. Substantial headway has been made in deciphering miRNAs’ roles in establishment, maintenance and exit from pluripotency in ES cells. Here, we summarize current and ongoing research on microRNAs’ roles of pluripotency maintenance and germ layer specification and possible mechanism to script the cell fate.
Keywords: pluripotency